Tuberculosis epidemiology in Cabo Verde from 2006 to 2016 - Silvânia Da Veiga Leal; Isaías Varela; Tomás Alves de Só Valdez (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2021)
Tuberculosis is an infectious disease usually caused by the bacteria Mycobacterium tuberculosis. This study aimed to analyze the epidemiological profile of Tuberculosis in Cabo Verde from 2006 to 2016. This is an epidemiological, longitudinal and descriptive study in which the secondary data on Tuberculosis were obtained from the annual statistical reports of the Ministry of Health. Incidence, prevalence, mortality rate and percentage of new cases of Tuberculosis, were calculated by age group, gender and treatment for each year. During the study period, 3 282 new cases of all forms of Tuberculosis were registered. The average annual incidence rate was 59 / 100,000. It was observed a higher incidence of the disease among men in the age group of 25 to 34 years old. Pulmonary Tuberculosis was the most frequent form of tuberculosis. The mortality rate in this period remained stable. Although there are positive effects from Tuberculosis control measures in the country, there is the need for complementary measures by developing active surveillance, strengthening the laboratory diagnosis capacity in order to reduce the disease prevalence and prevent multi-drug-resistant Tuberculosis. Moreover, there is a need for complementary epidemiological studies.